2015
DOI: 10.1111/nmo.12701
|View full text |Cite
|
Sign up to set email alerts
|

Localization and expression of TRPV1 and TRPA1 in the human oropharynx and larynx

Abstract: TRPV1 and TRPA1 are widely expressed in the human oropharynx with two distinct patterns. Our study further confirms that TRPV1/A1 receptors are promising therapeutic targets to develop active treatments for OD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 49 publications
1
47
1
Order By: Relevance
“…It is known that free nerve endings penetrate the epithelium in the skin, but there is little evidence about their presence within the oropharyngeal epithelium. The evidence collected in our review and many of our experiments on human tissue indicate a dense submucosal innervation in contrast to scarce cases of intraepithelial fibers (Fig. S1).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is known that free nerve endings penetrate the epithelium in the skin, but there is little evidence about their presence within the oropharyngeal epithelium. The evidence collected in our review and many of our experiments on human tissue indicate a dense submucosal innervation in contrast to scarce cases of intraepithelial fibers (Fig. S1).…”
Section: Discussionmentioning
confidence: 68%
“…In the oral cavity and oropharynx, TRPV1 has been detected at both the mRNA and protein levels in the tongue mucosa in nerve terminals and epithelial cells; immunoreactivity to TRPV1 has also been found in nerve fibers innervating the human larynx . A recent study also found TRPV1 expression in the mucosa of the human tongue, pharynx, and epiglottis and TRPV1 immunoreactivity on the membranes of epithelial cells of these regions, as well as on nerve fibers and leukocytes (Fig. S3).…”
Section: Receptors For Chemosensation and Thermosensationmentioning
confidence: 70%
“…All of these studies included groups of patients with poststroke OD, where these agonists showed significant effects on VFS signs of swallow response. We also recently studied the expression of TRPV1/A1 receptors in the human oropharynx, further confirming that these receptors are promising therapeutic targets to develop active treatments for OD patients …”
Section: Advances In Treatmentmentioning
confidence: 64%
“…TRPA1 was also expressed in all studied regions but was always localized below the basal lamina. No immunoreactivity for TRPA1 was found on epithelial cells . Preliminary studies from our group show that the cortical activation of stroke patients with OD in response to pharyngeal electrical stimulus is delayed compared with healthy volunteers.…”
Section: Advances In the Pathophysiology Of Poststroke Odmentioning
confidence: 80%
“…SP is released by activation of transient receptor potential vanilloid 1 (TRPV1), which is expressed in the oral mucosa, gastrointestinal (GI) tract mucosa, and airway mucosa [20]. TRPV1 is considered to be a therapeutic target of OD [21]. Capsaicin is a specific agonist to TRPV1, and it has occasionally been reported that administration of capsaicin improves OD [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%